Reducing Sachet Noodle Defects by Applying the Seven Tools and the FMEA Method - Andri Iriyanto; Cicilia Sriliasta Bangun; Arief Suwandi; Roesfiansjah Rasjidin (Dinasti Research, 2024)
The ICBP is a company that produces the noodle’s sachet on a large scale for domestic and international markets. The sachet’s defect of the Regular Special Fried Noodle for the Saudi Arabia market from January up to December 2023 is 2.39%, which is above the company's standard limit. The aim of this research is to determine the types of defects, and to find out the factors that caused them and find out the solutions to minimize the number of defects. Analysis using the seven tools identified that the most dominant defect is swallen laminate, with a percentage of 51% of total defects. By using the Failure Mode and Effect Analysis (FMEA) method, the highest RPN value was obtained at 280 for the machine factor. The recommended solution is to clean up the die lip thoroughly to ensure the condition of the die lip remains clean, to recalculate the need for a Preventive Maintenance schedule and calibration of the die lips based on machine age and machine usage working hours, and at the same time provide SOP and scheduled training for employees to make sure they know how to do the job.